A Rare Case of Multiple Subserous Uterine Adenomyomas Misdiagnosed as an Ovarian Cyst, Diagnosed and Treated by Laparoscopy - Fei H; Guo X; Li J; Jin X (International Journal of Women's Health)
Huali Fei,1 Xiaoyan Guo,2 Jin Li,2 Xuejing Jin1 1Department of Reproductive Endocrinology, Hangzhou Women’s Hospital, Hangzhou, People’s Republic of China; 2Department of Gynecology, Hangzhou Women’s Hospital, Hangzhou, People’s Republic of ChinaCorrespondence: Xiaoyan Guo, Department of Gynecology, Hangzhou Women’s Hospital, Hangzhou, People’s Republic of China, Email 19106735800@163.comObjective: To report a rare case of multiple subserous uterine adenomyomas diagnosed and treated by laparoscopy.Case Report: A premenopausal 55-year-old woman was admitted presenting with bilateral adnexal cysts. Preoperative ultrasound and magnetic resonance imaging both indicated a right ovarian cyst. However, during the laparoscopic surgery, it was identified that the cyst was multiple subserosal uterine cystadenomas, which were located on the posterior wall of the uterus and adjacent to the right ovary. Postoperatively, the pathology revealed that it was a subserosal uterine cystadenoma.Conclusion: Subserous adenomyomas, a rare subtype of uterine adenomyomas, are commonly reported in the literature as a single adenomyoma. Furthermore, no studies have reported the presence of multiple subserosal adenomyomas. This condition requires attention, and it is essential to differentiate it from ovarian cysts. Subserosal adenomyomas exceeding 8 cm in diameter are rare, with the literature documenting a mere six cases. Larger cysts are associated with a higher likelihood of malignancy. There is currently no effective drug treatment available for this disease. Laparoscopy is an effective method for treating this condition.Keywords: adenomyoma, adenomyosis, giant cystic adenomyoma, hysteroscopy